2003
DOI: 10.1146/annurev.micro.57.030502.090759
|View full text |Cite
|
Sign up to set email alerts
|

The Uncultured Microbial Majority

Abstract: Since the delineation of 12 bacterial phyla by comparative phylogenetic analyses of 16S ribosomal RNA in 1987 knowledge of microbial diversity has expanded dramatically owing to the sequencing of ribosomal RNA genes cloned from environmental DNA. Currently, only 26 of the approximately 52 identifiable major lineages, or phyla, within the domain Bacteria have cultivated representatives. Evidence from field studies indicates that many of the uncultivated phyla are found in diverse habitats, and some are extraord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
1,147
2
27

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,700 publications
(1,201 citation statements)
references
References 122 publications
(131 reference statements)
25
1,147
2
27
Order By: Relevance
“…Most of these studies depended on spore morphology and/or culture dependent methods for identification. As a majority of fungi are not readily cultured (Pace, 1997;Rappé and Giovannoni, 2003;Fröhlich-Nowoisky et al, 2009) or easily identified by spores alone (Burge, 1985), these results are expected to be an underestimation of airborne fungal diversity (Wu et al, 2004). Metagenomics, a new field in biology, uses new DNA sequencing technologies (e.g., pyrosequencing) to directly sequence and identify environmental microbes (Riesenfeld et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies depended on spore morphology and/or culture dependent methods for identification. As a majority of fungi are not readily cultured (Pace, 1997;Rappé and Giovannoni, 2003;Fröhlich-Nowoisky et al, 2009) or easily identified by spores alone (Burge, 1985), these results are expected to be an underestimation of airborne fungal diversity (Wu et al, 2004). Metagenomics, a new field in biology, uses new DNA sequencing technologies (e.g., pyrosequencing) to directly sequence and identify environmental microbes (Riesenfeld et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although culture-dependent strategies for the discovery of natural products have been very rewarding, this approach has likely missed the vast majority of naturally occurring bacterial metabolites. Only a tiny minority of the microbes present in nature is actually cultured using standard microbiological methods 2 . Even though most bacteria are not readily cultured in the laboratory, it is possible to extract microbial DNA directly from the naturally occurring consortia of bacteria present in environmental samples (environmental DNA (eDNA)).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity and precision increase from 92% and 93% on data with identical abundance levels to 97% and 99% on data with varying abundance levels. In order to explain this (somewhat counter-intuitive) phenomenon, we analyzed intermediate results, and found that two of the six pairs of genomes, (1,3) and (2,4), have high percentages of common repeats. These common repeats negatively affected the result on data with identical abundance levels.…”
Section: The Issue Of Abundance Levelsmentioning
confidence: 99%